2009
DOI: 10.1158/1055-9965.epi-08-0923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coffee and Green Tea Consumption on the Risk of Liver Cancer: Cohort Analysis by Hepatitis Virus Infection Status

Abstract: In spite of their anticarcinogenic potential, the effect of coffee and green tea consumption on the risk of liver cancer has not been clarified prospectively in consideration of hepatitis C (HCV) and B virus (HBV) infection. We examined whether coffee and green tea consumption was associated with a reduced risk of liver cancer by hepatitis virus infection status in the Japan Public Health Center-Based Prospective Study Cohort II. A total of 18,815 subjects ages 40 to 69 years participating in a questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 36 publications
6
92
3
1
Order By: Relevance
“…In various studies including a large prospective study, patients with HCV-related liver disease with a regular coffee consumption show a lower rate of disease progression such as hepatic fibrosis [131][132][133] and HCC [134][135][136][137][138] . Recently, it was also reported that more than 3 cups per day coffee drinkers are three times more likely to have a virological response to peginterferon plus ribavirin treatment than non-drinkers [139] .…”
Section: Coffee Consumptionmentioning
confidence: 99%
“…In various studies including a large prospective study, patients with HCV-related liver disease with a regular coffee consumption show a lower rate of disease progression such as hepatic fibrosis [131][132][133] and HCC [134][135][136][137][138] . Recently, it was also reported that more than 3 cups per day coffee drinkers are three times more likely to have a virological response to peginterferon plus ribavirin treatment than non-drinkers [139] .…”
Section: Coffee Consumptionmentioning
confidence: 99%
“…4 In the Japan Public Health Center-Based Prospective Study Cohort II, which included 18,815 subjects followed for 13 years and 110 incident cases of liver cancer affected by HCV or hepatitis B virus (HBV), the RRs were 0.67 for fewer than one cup per day, 0.49 for one to two cups, and 0.54 for three or more cups of coffee per day. 5 We computed the summary RRs and the corresponding CIs for coffee drinkers, and for various levels of coffee consumption versus nondrinkers, applying the same methods of the previous metaanalysis. 1 Briefly, we performed a Medline search of the literature from 1966 to June 2009, using the MeSH terms "coffee" and combinations of "hepatocellular" or "liver" and "carcinoma" or "neoplasm."…”
mentioning
confidence: 99%
“…Theses capsules are usually taken more than one a day. Furthermore, United Kingdom tea council has recommended intake of 3-4 cups of tea per day for health benefits and intake of >6 cups of tea is not beneficial to health (58)(59)(60)(61)(62)(63).…”
Section: Harmful Effectsmentioning
confidence: 99%